Mechanical Behavior of Fly-Ash Geopolymer Under Stray-Current and Soft-Water Coupling - Ran Tang; Fang Liu; Baoming Wang; Xiaojun Wang; Cheng Hua; Xiaosa Yuan (Buildings, 2025)
Stray-current and soft-water leaching can induce severe corrosion in reinforced concrete structures and buried metal pipelines within subway environments. The effects of water-to-binder ratio (W/C), modulus of sodium silicate (Ms), and alkali content (AC) on the mechanical properties of fly-ash-based geopolymer (FAG) at various curing ages were investigated. The influence of curing temperature and high-temperature curing duration on the development of mechanical performance were examined, and the optimal curing regime was determined. Furthermore, based on the mix design of FAG resistant to coupled erosion from stray-current and soft-water, the effects of stray-current intensity and erosion duration on the coupled erosion behavior were analyzed. The results indicated that FAG exhibited slow strength development under ambient conditions. However, thermal curing at 80 °C for 24 h markedly improved early-age strength. The compressive strength of FAG exhibited an increase followed by a decrease with increasing W/B, Ms, and AC, with optimal ranges identified as 0.28–0.34, 1.0–1.6, and 4–7%, respectively. Soft-water alone caused limited leaching, while the presence of stray-current significantly accelerated degradation, with corrosion rates increasing by 4.1 and 7.2 times under 20 V and 40 V, respectively. The coupled corrosion effect was found to weaken over time and with increasing current intensity. Under coupled leaching conditions, compressive strength loss of FAG was primarily influenced by AC, with lesser contributions from W/B and Ms. The optimal mix proportion for corrosion resistance was determined to be W/B of 0.30, Ms of 1.2, and AC of 6%, under which the compressive strength after corrosion achieved the highest value, thereby significantly improving the durability of FAG in harsh environments such as stray-current zones in subways.